2011
DOI: 10.1242/jeb.061358
|View full text |Cite
|
Sign up to set email alerts
|

Cues to body size in the formant spacing of male koala (Phascolarctos cinereus) bellows: honesty in an exaggerated trait

Abstract: SUMMARYDetermining the information content of vocal signals and understanding morphological modifications of vocal anatomy are key steps towards revealing the selection pressures acting on a given species' vocal communication system. Here, we used a combination of acoustic and anatomical data to investigate whether male koala bellows provide reliable information on the caller's body size, and to confirm whether male koalas have a permanently descended larynx. Our results indicate that the spectral prominences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 79 publications
8
116
0
Order By: Relevance
“…Other species produce abnormally low formants for their size by extending their vocal tracts using descended and/or mobile larynges (red deer, Cervus elaphus, Reby and McComb, 2003;fallow deer, Dama dama, McElligott et al, 2006; Mongolian gazelle, Procapra gutturosa, Frey et al, 2008; goitred gazelle, Gazella subgutturosa, Frey et al, 2011;koala, Charlton et al, 2011; roaring cats, Panthera sp., Weissengruber et al, 2002), air sacs (black and white colobus monkey, Colobus guereza, Harris et al, 2006) and nasal proboscises (African elephant, Loxodonta africana, McComb et al, 2003;saiga, Saiga t. tatarica, Frey et al, 2007; elephant seals, Mirounga leonina, Sanvito et al, 2007). These anatomical adaptations are thought to evolve via selection pressures for individuals to lower frequency components, either to broadcast an exaggerated impression of their body size in reproductive contexts or to maximise signal propagation in the species' natural environment (koala, Charlton et al, 2011Charlton et al, , 2013red deer, Fitch and Reby, 2001;Reby and McComb, 2003;fallow deer, Vannoni and McElligott, 2008;bison, Bison bison, Wyman et al, 2012). In contrast, some animal species, such as sika deer, Cervus nippon (Minami and Kawamichi, 1992), appear to have evolved the ability to produce relatively higher pitched vocalisations than expected for their body size.…”
Section: Introductionmentioning
confidence: 99%
“…Other species produce abnormally low formants for their size by extending their vocal tracts using descended and/or mobile larynges (red deer, Cervus elaphus, Reby and McComb, 2003;fallow deer, Dama dama, McElligott et al, 2006; Mongolian gazelle, Procapra gutturosa, Frey et al, 2008; goitred gazelle, Gazella subgutturosa, Frey et al, 2011;koala, Charlton et al, 2011; roaring cats, Panthera sp., Weissengruber et al, 2002), air sacs (black and white colobus monkey, Colobus guereza, Harris et al, 2006) and nasal proboscises (African elephant, Loxodonta africana, McComb et al, 2003;saiga, Saiga t. tatarica, Frey et al, 2007; elephant seals, Mirounga leonina, Sanvito et al, 2007). These anatomical adaptations are thought to evolve via selection pressures for individuals to lower frequency components, either to broadcast an exaggerated impression of their body size in reproductive contexts or to maximise signal propagation in the species' natural environment (koala, Charlton et al, 2011Charlton et al, , 2013red deer, Fitch and Reby, 2001;Reby and McComb, 2003;fallow deer, Vannoni and McElligott, 2008;bison, Bison bison, Wyman et al, 2012). In contrast, some animal species, such as sika deer, Cervus nippon (Minami and Kawamichi, 1992), appear to have evolved the ability to produce relatively higher pitched vocalisations than expected for their body size.…”
Section: Introductionmentioning
confidence: 99%
“…Although first discovered in two deer species (Fitch & Reby 2001), a permanently descended larynx has now been observed in various other mammals, including lions and other Panthera cats, koalas, and some ungulates (Charlton et al 2011, Frey & Riede 2003, Weissengruber et al 2002. This repeated convergent evolution of a descended larynx suggests some consistent selective force, and none of these other mammals produce speechlike variation in formant patterns.…”
Section: Peripheral Components Of Speech Productionmentioning
confidence: 98%
“…More research is therefore needed to determine if humans use the same processing mechanisms to judge the pitch-size cues in voices as they do to determine the size of environmental objects. Charlton et al, 2011). However, whilst in some mammal species the formant structure can predict a large amount of the variance in body weight (e.g., 62% across dog breeds due to their high level of morphological variation; Taylor et al, 2008), in humans formant related estimates of vocal tract length account for only around 10% of the variance in height and weight for adult men and women (Pisanski et al, 2014), which may be related to the high level of vocal tract flexibility shown during speech production (Cartei et al, 2012;Collins, 2000;Puts et al, 2006).…”
Section: Statistical Correspondencesmentioning
confidence: 99%